2020
DOI: 10.1016/s1473-3099(20)30589-2
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of COVID-19 in health-care workers in Denmark: an observational cohort study

Abstract: Summary Background Health-care workers are thought to be highly exposed to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We aimed to investigate the prevalence of antibodies against SARS-CoV-2 in health-care workers and the proportion of seroconverted health-care workers with previous symptoms of COVID-19. Methods In this observational cohort study, screening was offered to health-care workers in the Capital Region of Denmark, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

71
437
17
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 402 publications
(558 citation statements)
references
References 18 publications
(30 reference statements)
71
437
17
8
Order By: Relevance
“…In conclusion, HCWs in this study were at modestly lower risk for SARS-CoV-2 infection as compared with other studies of HCWs from the New York area and Spain, and similar seropositive rates as reported in Denmark [ 4 , 22 , 23 ]. Across occupation groups, nurses were at the highest-level risk from work-related exposures.…”
Section: Discussionsupporting
confidence: 85%
“…In conclusion, HCWs in this study were at modestly lower risk for SARS-CoV-2 infection as compared with other studies of HCWs from the New York area and Spain, and similar seropositive rates as reported in Denmark [ 4 , 22 , 23 ]. Across occupation groups, nurses were at the highest-level risk from work-related exposures.…”
Section: Discussionsupporting
confidence: 85%
“…These rates are significantly higher than those found within the general population (38.5% and 30.4%, respectively, according to a recent meta-analysis) 9 and equally considerably higher when compared to HCW prevalence rates in the United States 11,12 or in other European countries. 13,14 In addition, a higher rate of dysgeusia was particularly highlighted in our European cohort which had not been previously described. The higher prevalence rates of both olfactory and taste disturbance are unexpected when T A B L E 4 Influence of available variables on recovery rate in the population of health care workers who experienced smell and/or taste dysfunction First Symptom P = .6 P = .9 P = .7 P = .6 P = .7 P = .9…”
Section: Discussionsupporting
confidence: 43%
“…This suggests a risk similar to that of the general Danish population (1 July 12 831 COVID-19 infected/total population 5.8 mill=0.22%) ( www.SSI.dk ). 15 Similarly, previous studies have found no evidence of an overrepresentation of patients with inflammatory rheumatic disease among SARS-CoV-2 infected. 2–4 …”
Section: Discussionmentioning
confidence: 78%